Enamel fracture in the primary dentition has no impact on children's quality of life: implications for clinicians and researchers. Issue 2 (23rd September 2015) - Feldens, Carlos Alberto; Day, Peter; Borges, Tássia Silvana; Feldens, Eliane Gerson; Kramer, Paulo Floriani
Abstract: Aim: The aim of this study was to quantify the impact of traumatic dental injuries (TDI) on oral‐health‐related quality of life (OHRQoL) of preschool children, when enamel fractures were either included or excluded within the category of TDI. Material and methods: An oral health survey was undertaken of preschool children, age 1–5 years attending public nurseries in Canoas, Brazil. Children were examined for TDI, dental caries, and malocclusion. Parents were interviewed on their perception of their child's OHRQoL (Early Childhood Oral Health Impact Scale—ECOHIS) and their sociodemographic background. Multivariable Poisson regression models with robust variance were fitted to assess the impacts of TDI (including and excluding enamel fractures) on OHRQoL. Results: A full dataset was collected from 76% of the eligible population. The prevalence of TDI was 13.4% (171/1275). The prevalence of any impact (ECOHIS ≥ 1) was significantly higher in children with crown discoloration (29.7%), enamel/dentin fracture (29.2%), and avulsion (73.3%), compared to children with enamel fracture (16.2%) or without a TDI (15.8%) ( P  < 0.001). Enamel fractures were the most prevalent TDI (40%) but halved the proportion of children with a reported impact from their TDI. The mean increase in OHRQoL impact for those children with a TDI was 1.59 (95%CI 1.20–2.10) when enamel fracture was included, and 1.86 (95%CI 1.39–2.50) when it was excluded. Conclusion: Enamel fractures have no significant impact on young children's quality of life. Including enamel fractures within the diagnosis of TDI increases the prevalence of TDI while reducing the OHRQoL impact of TDI for the primary dentition.